2006
DOI: 10.1300/j013v43n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Effective Contraceptive Use Among a Sample of Latina Women

Abstract: Unintended pregnancy disproportionately affects Latina women. One factor contributing to unintended pregnancy among Latinas is the low rate of contraceptive use. This study examined correlates of effective contraceptive use among a sample of Latina women (n=202) at increased risk for HIV. In addition to traditional intrapersonal variables (i.e., perceived risk of pregnancy, motivation to avoid pregnancy), the present study examined the role of the male partner and relationship factors (i.e., relationship commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Evidence on how relationship type influences contraceptive use is also mixed among adults [7,912]. Women in erratic relationships may be less likely than others to plan sexual intimacy, leaving them unprepared to protect against pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on how relationship type influences contraceptive use is also mixed among adults [7,912]. Women in erratic relationships may be less likely than others to plan sexual intimacy, leaving them unprepared to protect against pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here Diego is involved and supportive in discussing contraceptive options with his partner prior to choosing injectable contraception; yet, similar to many of the other interviewed men, he downplayed his involvement to distance himself from domineering expressions of masculinity in contraception, such as forcing a woman to use a method; this is in contrast to prior research showing that when men engage in reproductive coercion it is often to prevent contraceptive use (Harvey, Henderson, and Casillas 2006; Northridge et al 2017; Tschann et al 2002). While acknowledging deference to his girlfriend’s decision-making power reflects his respect for her bodily agency and his effort to work against structural barriers, Diego’s words also convey a feminized responsibility for pregnancy prevention.…”
Section: Men’s Engagement In Contraceptive Managementmentioning
confidence: 81%
“…Dominant cultural ideals for masculinity in the context of young men’s health tend to encourage men’s unhealthy risk-taking (Addis and Mahalik 2003; Connell 2005; de Visser and Smith 2006; de Visser, Smith, and McDonnell 2009) and contraception-avoidant behaviors (Oudshoorn 2004). Prior empirical work has shown that when men do engage in contraceptive management they often work against its use, particularly with condoms (Harvey, Henderson, and Casillas 2006; Tschann et al 2002). This interference typically does not reflect men’s pregnancy intentions but is often to exert dominance over women (Kane and Schippers 1996; Miller, Jordan, et al 2010; Upadhyay et al 2014).…”
mentioning
confidence: 99%
“…The ability to talk about risk reduction and prevention of STIs with a sexual partner has been examined in several studies (e.g., Catania et al, 1992;Catania, Kegeles, & Coates, 1990;Dolcini, Coates, Catania, Kegeles, & Hauck, 1995;Harvey, Henderson, & Casillas, 2006;Sheeran, Abraham, & Orbell, 1999). The intention to engage in conversations with partners about risk and prevention is a prerequisite for negotiating actual use of preventive measures (e.g., STI testing, use of male condom).…”
Section: Discussionmentioning
confidence: 99%